Ionospheric Es layer scintillation characteristics studied with Hilbert-Huang transform. Issue 10 (15th November 2019) - Su, S.-Y.; Tsai, L.-C.; Liu, C.H.; Nayak, C.; Caton, R.; Groves, K.
Abstract: A coincident event of daytime ionospheric Es layer scintillation observations is analyzed with the Hilbert-Huang transform (HHT) to study its layer structure. One of the coincident observations is made by a radio beacon passing through the Es layer at a slant angle received by the SCINDA (Scintillation Decision Aide) receivers located at southern Taiwan. The data indicates that the Es layer consists of scattering blocks of  ∼ 650 to 970 m in size as revealed in the dominant components of the HHT analysis. The time shift in the two spaced receiving antennas implies that the daytime E region westward drift is about 36 m/s. On the other hand, the same Es layer is observed by the radio occultation (RO) experiment with the L1 signal from the Global Positioning System (GPS) satellites to the FORMOSAT-3/Constellation-Observing-System-for-Meteorology (FS-3/COSMIC) satellites. The GPS L1 signal passes through the Es layer horizontally. The observed signal variations reveal a dense slab structure that blocks the L1 signal to cause a diffraction pattern. The slab thickness in the vertical direction is about 780 m. The HHT analyses of the coincident observations thus conclude that the observed daytime Es layer has a vertical dense slab structure and patches of scattering blocks in the horizontal structure.